Reformulation of competency development of lecturers of state Islamic religious universities in Indonesia after COVID-19 / Mujiburrahman ... [et al.] - ., Mujiburrahman; ., Zulfatmi; ., Sabirin; Khatimah, Husnul; Husen Ismail, Faisal (Universiti Teknologi MARA, 2022)
The study of the competency of lecturers in Indonesia cannot be separated from the study of state intervention in education. State hegemony occurs in the form of formalization of regulations governing the improvement of capabilities and competences of lecturers. Research shows that the presence of Law No. 14 of 2005 and Government Regulation No. 37 of 2009 has been used as an implementation juridical foothold to encourage the increase of qualifications and competences of lecturers at State Islamic Religious Colleges (PTKIN) in Indonesia in general, and in UIN Ar-Raniry and UIN Bandung specifically. A qualitative-quantitative combination research design was applied in this research with data set approaches through documentation studies, observations, in-depth interviews, and questionnaires. This research establishes that the development of lecturer competence in PTKIN is in line with and not contradictory to the national education system and strengthens the content of Law No. 14 of 2005 and Government Regulation No. 37 of 2009. The qualifications and competences of lecturers at PTKIN have improved, but there is still a treat of implementation of regulations that have not been maximally felt by the lecturers. Upgrading the qualifications and competences of lecturers well and maximally, substantially affects PTKIN lecturers in improving the performance, professionalism and quality of academic benefits for students. These logical consequences have a positive impact on the transformation of education in the PTKIN environment after COVID-19, where learning processes and academic services can run online based on information technology.